Interest Rate Behavior and Financial Sector's Growth: A Relationship Analysis - Ogunlokun, Ayodele; Oguntuase, Taiwo (Acta Universitatis Danubius. Œconomica, 2023)
ABSTRACTThe behavioral effect of interest rates was investigated in this study. From secondary sources, the study collected quantitative data from 1987 to 2020. The modeled the growth of the financial sector, proxy by the real Gross Domestic Product of the sector as a linear function interest rate, proxy by lending interest rate, deposit interest rate, monetary policy rate and treasury bill rate. Furthermore, as the Philip-Peron approach to unit root test revealed that the variables were integrated of I(0) and I(1), Autoregressive Distributed Lags model was specified and estimated with conitegration bound test which reveled evidence of long run relationship among the variables. The result showed that lending interest rate, with coefficient -0.1391LIR and p-value = 0.0268<0.05 was the most significant influencer of the growth in the financial sector while deposit interest rate with -0.0076 coefficient and p-value = 0.7410>0.05, monetary policy rate with 0.0077 coefficient and p-value = 0.2626>0.05 and treasury bill rate with -0.3533 coefficient and p-value = 0.4889>0.05 were not weak in influencing the growth of the financial sector in the long run, although the relationships exhibited by these variables differs slightly in the short run. in addition, the error correction mechanism revealed that any temporary deviation from the equilibrium experienced by the interest rate proxies adjusted quickly to the equilibrium in the long run at the speed of 35%. Also, the post-estimation test revealed that the residuals were homoscedastic while the autocorrelation test revealed that the residuals were uncorrelated. Hence, the study concluded that lending interest rate was a significant determinant of the growth in the financial sector and recommended that since th financial sector is deregulated already, lending interest rate should be naturally allowed to be dictated by the market forces of demand and supply rather than being artificially fixed by the banks which often take advantage of this to extort customers; this will weaken the current significant negative effect which lending rate has on the growth of the financial sector.Key Words: Interest rate, financial sector, growth, long-run